2015
DOI: 10.1007/s10934-015-9950-8
|View full text |Cite
|
Sign up to set email alerts
|

para-Selectivity of silicalite-1 coated MFI type galloaluminosilicate in aromatization of light alkanes

Abstract: MFI type galloaluminosilicates (GaAlMFI) were coated with inert silicalite-1 layers. The silicalite-1 coating could improve the para-selectivity for xylene production in aromatization of propane. In the silicalite-1 coating step, low alkali concentration in the synthesis solution enhanced para-selectivity. A proton-exchange procedure also had an impact on the para-selectivity. Significant decrease of para-selectivity was observed over the silicalite-1 coated GaAlMFI with repeated proton-exchange. From the 71 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…[4][5][6][7][8][9] Impregnation of metals into the ZSM-5 structure enhances aromatization selectivity in such a way that the acidity of ZSM-5 provides the cracking, while metal function is responsible for dehydrogenation, which converts olefins into aromatics. [10,11] Moreover, the metal component reduces severe cracking selectivity toward lower paraffin's and produces hydrogen as by-product. The effect of modified gallium and zinc HZSM-5 catalysts for n-hexane and light naphtha on aromatization has been studied by several research groups.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Impregnation of metals into the ZSM-5 structure enhances aromatization selectivity in such a way that the acidity of ZSM-5 provides the cracking, while metal function is responsible for dehydrogenation, which converts olefins into aromatics. [10,11] Moreover, the metal component reduces severe cracking selectivity toward lower paraffin's and produces hydrogen as by-product. The effect of modified gallium and zinc HZSM-5 catalysts for n-hexane and light naphtha on aromatization has been studied by several research groups.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, silicalite-1 (Al-free MFI type zeolite) coated catalysts showed much higher catalytic performance on various reaction systems [38][39][40][41][42][43][44][45][46] .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we synthesized various core-shell structured materials. [54][55][56][57][58][59][60][61][62][63][64][65] In particular, we demonstrated that thin carbon shells (graphene) were deposited on P25 (commercially available and inexpensive TiO 2 ) by chemical vapour deposition (CVD) using methanol or propylene as carbon source. [65] In addition, we prepared Co nanoparticles modified carbon nanotubes with good ORR catalytic performance using poly vinyl pyrrolidone (PVP) as a protecting agent and NaBH 4 as a reduction agent.…”
Section: Accepted Manuscriptmentioning
confidence: 99%